CHANGES IN THE LEVEL OF NATRIURETIC PEPTIDES IN PATIENTS WITH ATRIAL FIBRILLATION TREATED WITH ANTIARRHYTHMIC DRUGS - V. I. Podzolkov; A. I. Tarzimanova; I. Z. Loriya (Столичная издательская компания, 2015)
Aim. To study the changes of plasma levels of NT-proBNP and NT-proANP in patients with persistent atrial fibrillation (AF) treated with various antiarrhythmic drugs.Material and methods. Patients with persistent AF (n=123) aged 39-83 years old were included into the study. The patients were divided into 2 groups: group 1 included patients with arterial hypertension (n=61), group 2 - patients with ischemic heart disease (IHD; n=62). After sinus rhythm restoration the patients were divided into 4 subgroups. Patients of 1A subgroup used propafenone to maintain sinus rhythm during the next 6 months, while patients of 2A subgroup used amiodarone. Patients of 1B and 2B subgroups used bisoprolol to control ventricular rate. Plasma natriuretic peptide levels were evaluated in all patients during the first 3 days after the sinus rhythm restoration and 6 months after.Results. Increased levels of NT-proBNP and NT-proANP in the first days after the sinus rhythm restoration were found in patients of both groups and were associated with the episode of AF. After 6 months of treatment the reduction of NT-proBNP and NT-proANP levels was found in patients of 1A subgroup (NT-proBNP: from 160.5±15.2 pg/ml to 130.1±12.2 pg/ml; NT-proANP: from 15.3±6.4 nmol/L to 11.5±5.3 nmol/L, p<0.05 for both) and of 2A subgroup (NT-proBNP: from 180.2±12.7 to 120.6±10.9 pg/ml; NT-proANP: from 17.1±7.1 to 11.8±7.2 nmol/L, p<0.05 for both). NT-proBNP and NT-proANP levels were decreasing consistently both in hypertensive patients receiving propafenone and in IHD patients taking amiodarone. No significant changes in NT-proBNP and NT-proANP levels were found in patient of subgroups 1B and 2B during the follow-up.Conclusion. Increased plasma levels of NT-proBNP and NT-proANP were found in the first days after the restoration of sinus rhythm in patients with persistent AF, and after 6 months of sinus rhythm maintenance these levels reduced significantly.